Determination of Dry Rubber Content of Hevea Latex by Microwave Technique - Khalid, Kaida (1982)
The measurement of the dry rubber content of the fresh hevea latex by microwave technique is described. In this technique the attenuation of microwave by latex is measured at 10.7 GHz and is then calibrated against the standard laboratory method. Compared with the standard method this instrument is able to reduce the measuring time 8 - 16 hours to three minutes. The correlation coefficient between the DRC determined using this instrument and the standard laboratory method is 0.998 and the standard deviation is less than 0.7%. The reproducibility is at a level of 0.8% unit DRC.